THE ISSUE OF CONCEPTUAL EQUIVALENCE IN THE TRANSLATION OF E. HEMINGWAY`S NOVELS INTO AZERBAIJANI - Azad MAMMADOV; Nigar BABAYEVA (Езиков свят)
The hypothesis in the paper is that conceptual equivalence as one of the key types of equivalence between the source and the target texts can be achieved not only based on translation strategies in the elements of figurative language such as metaphor, but also based on translation strategies in the elements of literal language. Analysis of these strategies can offer the translator rich information on the linguistic choices of the author of the source text and how the translator considers these choices depending on cognitive perspectives of all participants of the discourse of translation. In this connection, the paper aims to revisit this topic by exploring the role of various elements of literal and figurative language in the process of reconceptualization of the source text into the target text as cycles of reconceptualization. The ultimate goal is to demonstrate the ways how the translator uses these elements in the process of achieving conceptual equivalence between the source and the target texts especially when these two texts belong to genealogically, typologically and culturally different languages (English and Azerbaijani). The results of the study can help understand better the role of universal and culture- specific aspects in the production of the discourse of translation.